Ethics and bioethics in telemedicine in primary health care - da Cruz, Andrey Oliveira (2021)
Telemedicine in primary health care through the National Telehealth Brazil Networks Program emerged as a technological tool to support health professionals in the follow-up of patients in the Unified Health System. This paper reports the experience of using the program in primary careand discusses the ethical and bioethical implications involved in the mandatory adherence of the program to the local regulatory system to reduce referral queues and organize access to specialized services. Difficulties in user access to specialized health care, limitations to medical autonomy and conflicts in the doctor-patient relationship were identified. The use of telemedicine in primary care presents different ethical and bioethical aspects that need to be analyzed. In addition, it lacks its own legislation and standards to ensure the rights of patients and value the doctor-patient relationship, as well as the work of the medical professional who works at the Unified Health System gateway.